後方散乱光による中性脂肪無侵襲計測の基礎的検討 - 王, 磊; 清水, 孝一; 飯永, 一也; 加藤, 祐次 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
For the diagnosis of postprandial hyperlipidemia, it is necessary to measure the temporal change of the serum triglyceride level by sampling the blood frequently. To solve this problem, we have developed an optical technique to evaluate the scattering property of the blood serum noninvasively. The scattering coefficient can be measured by the spatially resolved measurement of backscattered light with the diffusion approximation for light propagation. However, this approximation is not necessarily valid for the blood. In this study, we can estimate the scattering coefficient accurately even with the human blood (μa =0.5 /mm).